Kentucky Bluegrass Invasion in the Northern Great Plains and Prospective Management Approaches to Mitigate Its Spread - Rakhi Palit; Greta Gramig; Edward S. DeKeyser (Plants, 2021)
Kentucky bluegrass (Poa pratensis L.) is one of the most aggressive grasses invading Northern Great Plains (NGP) grasslands, resulting in substantial native species losses. Highly diverse grasslands dominated by native species are gradually transforming into rangelands largely dominated by non-native Kentucky bluegrass. Several factors potentially associated with Kentucky bluegrass invasions, including high propagule pressure, thatch formation, climate change, and increasing nitrogen deposition, could determine the future dominance and spread of Kentucky bluegrass in the NGP. Because atmospheric CO2 is amplifying rapidly, a C3 grass like Kentucky bluegrass might be photosynthetically more efficient than native C4 grasses. As this exotic species shares similar morphological and phenological traits with many native cool-season grasses, controlling it with traditional management practices such as prescribed fire, grazing, herbicides, or combinations of these practices may also impair the growth of native species. Thus, developing effective management practices to combat Kentucky bluegrass spread while facilitating the native species cover is essential. Modifying traditional techniques and embracing science-based adaptive management tools that focus on the ecological interactions of Kentucky bluegrass with the surrounding native species could achieve these desired management goals. Enhancement of the competitiveness of surrounding native species could also be an important consideration for controlling this invasive species.